Flexural Test on Recycled Polystyrene - Schmidt, P. N. S. [UNESP]; Cioffi, M. O. H. [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP]; Silveira, J. L. (Elsevier B.V., 2011)
In socio-environmental scenario increased the nature resources concern beyond products and subproducts reuse. Recycling is the approach for a material or energy reintroducing in productive system. This method allows the reduction of garbage volume dumped in environment, saving energy and decreasing the requirement of natural resources use. In general, the ending of expanded polystyrene is deposited sanitary landfills or garbage dumps without control that take large volume and spreads easily by aeolian action, with consequently environmental pollution, however, the recycling avoids their misuse and the obtainment from petroleum is reduced. This work recycled expanded polystyrene via merger and/or dissolution by solvents for the production of integrated circuits boards. The obtained material was characterized in flexural mode according to ASTM D 790 and results were compared with phenolite, traditionally used. Specimens fractures were observed by electronic microscopy scanning in order to establish patterns. Expanded Polyestirene recycled as well as phenolite were also thermo analyzed by TGA and DSC. The method using dissolution produced very brittle materials. The method using merger showed no voids formation nor increased the brittleness of the material. The recycled polystyrene presented a strength value significantly lower than that for the phenolite. (C) 2011 Published by Elsevier Ltd. Selection and peer-review under responsibility of ICM11
Keywords: Expanded Polystyrene; Recycling; Integrated Circuit Boards